2010
DOI: 10.1111/j.1365-3059.2010.02327.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of three distinct Polerovirus species and a recombinant Cucurbit aphid‐borne yellows virus strain infecting cucurbit crops in Taiwan

Abstract: To better understand the genetic diversity of cucurbit-infecting poleroviruses in Taiwan, a survey was conducted in 2008 and 2009 as a prelude to screening germplasm for resistance. Out of 102 cucurbit samples showing yellowing symptoms collected across eight counties, 29 were identified as infected by polerovirus(es) by reverse transcription polymerase chain reaction (RT-PCR) using a set of universal polerovirus primers. Sequence analysis of a 1AE4-kb PCR product spanning part of the RNA-dependent RNA polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 40 publications
4
49
0
8
Order By: Relevance
“…Apart from cucurbit crops, other species of agronomic importance that are CABYV hosts include Beta vulgaris and Lactuca sativa, as well as common weed species such as Capsella bursa-pastoris, Papaver rhoeas and Senecio vulgaris which are thought to be virus reservoirs (Knierim et al, 2010;Mnari-Hattab et al, 2009). CABYV is a phloem-limited virus that is transmitted in a persistent, non-propagative mode by aphids, including Aphis gossypii and Myzus persicae (Lecoq et al, 1992).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Apart from cucurbit crops, other species of agronomic importance that are CABYV hosts include Beta vulgaris and Lactuca sativa, as well as common weed species such as Capsella bursa-pastoris, Papaver rhoeas and Senecio vulgaris which are thought to be virus reservoirs (Knierim et al, 2010;Mnari-Hattab et al, 2009). CABYV is a phloem-limited virus that is transmitted in a persistent, non-propagative mode by aphids, including Aphis gossypii and Myzus persicae (Lecoq et al, 1992).…”
Section: Figurementioning
confidence: 99%
“…A 1.1 kb portion of the polerovirus genome was amplified from all 26 ELISApositive samples using the general polerovirus primer pair Pol-G-F and Pol-G-R in RT-PCR (Knierim et al, 2010). PCR amplicons were subsequently sequenced (GenBank Accession No.…”
Section: Figurementioning
confidence: 99%
“…A survey of literature on virus diseases of cucurbits revealed that more than 39 well characterized viruses are distributed in unrelated genera, such as Begomo virus, Crinivirus, Cucumovirus, Polerovirus, Tospovirus, Ipomovirus, Tobamovirus and Potyvirus, which are known to naturally infect cucurbits (Antignus et al, 2001;Salem et al, 2007;Kneirim et al, 2010;Gholamalizadeh et al, 2008;Brown et al, 2002;Owolabi et al, 2008Owolabi et al, , 2011Owolabi et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse transcription polymerase chain reaction (RT-PCR) was performed with primers Pol-G-F and Pol-G-R designed for universal detection of poleroviruses by amplifying parts of the RNA-dependent RNA polymerase (RdRp) and coat protein (CP) genes (Knierim et al, 2010). All 24 samples were positive following RT-PCR whereas healthy controls gave negative results.…”
Section: Figurementioning
confidence: 99%